2022
DOI: 10.1038/s41524-021-00682-7
|View full text |Cite
|
Sign up to set email alerts
|

Design of soft magnetic materials

Abstract: We present a strategy for the design of ferromagnetic materials with exceptionally low magnetic hysteresis, quantified by coercivity. In this strategy, we use a micromagnetic algorithm that we have developed in previous research and which has been validated by its success in solving the “Permalloy Problem”—the well-known difficulty of predicting the composition 78.5% Ni of the lowest coercivity in the Fe–Ni system—and by the insight it provides into the “Coercivity Paradox” of W. F. Brown. Unexpectedly, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…[1][2][3] On the other hand, it has been shown that nonzero magnetostriction can be beneficial for achieving low values of magnetic hysteresis in ferromagnetic films. [4,5] Ferromagnetic thin-film-based devices, especially magnetic field sensors, have numerous applications in the modern world, ranging from navigation systems to medical diagnostics and data storage applications. [6] These include magnetoresistive (XMR) sensors based on the anisotropic (AMR), [7][8][9] the giant (GMR), [10][11][12][13][14] and the tunnel magnetoresistive (TMR) [15][16][17] effects, mostly comprising magnetostrictive layer compositions for optimization of XMR effect strength or feasibility of fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] On the other hand, it has been shown that nonzero magnetostriction can be beneficial for achieving low values of magnetic hysteresis in ferromagnetic films. [4,5] Ferromagnetic thin-film-based devices, especially magnetic field sensors, have numerous applications in the modern world, ranging from navigation systems to medical diagnostics and data storage applications. [6] These include magnetoresistive (XMR) sensors based on the anisotropic (AMR), [7][8][9] the giant (GMR), [10][11][12][13][14] and the tunnel magnetoresistive (TMR) [15][16][17] effects, mostly comprising magnetostrictive layer compositions for optimization of XMR effect strength or feasibility of fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that soft magnetic properties can be designed by controlling magneto-elastic coupling [21,22,23]. Along these lines, the residual stress caused by AM and the underlying phase transitions could be key for tuning the coercivity in an AM-processed Fe-Ni permalloy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a vast number of calculations, the dimensionless constant (C 11 − C 12 )λ 2 100 /2K u ≈ 81 was proposed as a condition for low coercivity along the 100 crystalline direction for cubic materials (incl. Fe-Ni permalloy) [23]. Here, C 11 and C 12 are the components of the stiffness tensor, λ 100 is the magnetostrictive constant, and K u is the magneto-crystalline constant.…”
Section: Introductionmentioning
confidence: 99%
“…arXiv:2209.04070v1 [cond-mat.mtrl-sci] 9 Sep 2022 Contrary to this, some studies suggest the importance of in-plane MCA of magnetic materials for applications such as a magnetic under-layer of a perpendicular recording medium [4] and a spin torque oscillator for microwave-assisted magnetic recording (MAMR) [5,6]. Furthermore, the development of soft magnets requires extremely small MCA under distortion to eliminate losses caused by magnetic hysteresis and circulating loops of current [7]. Hence, understanding MCA is necessary for the development of novel magnetic materials.…”
Section: Introductionmentioning
confidence: 99%